2001
DOI: 10.1042/cs1010147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy and high-impact physical exercise on skeletal muscle in post-menopausal women: a randomized placebo-controlled study

Abstract: An age-related decline in muscle performance is a known risk factor for falling, fracture and disability. In women, a clear deterioration is observed from early menopause. The effect of hormone replacement therapy (HRT) in preserving muscle performance is, however, unclear. This trial examined the effects of a 12-month HRT and high-impact physical exercise regimen on skeletal muscle in women in early menopause. A total of 80 women aged 50-57 years were assigned randomly to one of four groups: exercise (Ex), HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
121
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 34 publications
10
121
4
3
Order By: Relevance
“…We have previously reported, in a larger study with the same study subjects, that leg extensor power, assessed by vertical jumping height, 23 and thigh muscle mass increased upon the use of HRT compared to the non-HRT group, where they decreased. 14 Parallel results were obtained with the smaller study sample used in microarray analysis, albeit the functional measurements did not reach statistical significance. Together these results suggest that during early postmenopause, when there is no counteracting medication available, the muscle transcriptome shows notable change; this, in turn, may be related to the deterioration in muscle characteristics in later life.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…We have previously reported, in a larger study with the same study subjects, that leg extensor power, assessed by vertical jumping height, 23 and thigh muscle mass increased upon the use of HRT compared to the non-HRT group, where they decreased. 14 Parallel results were obtained with the smaller study sample used in microarray analysis, albeit the functional measurements did not reach statistical significance. Together these results suggest that during early postmenopause, when there is no counteracting medication available, the muscle transcriptome shows notable change; this, in turn, may be related to the deterioration in muscle characteristics in later life.…”
supporting
confidence: 67%
“…14 The study sample was taken from postmenopausal women aged 50-57 years living in the city of Jyväskylä, Finland. Initially 118 women eligible for the study were invited for a clinical examination to assess hormonal menopausal status via serum steroid measurements (DELFIA, Wallac).…”
Section: Study Design and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERs are also found in the skeletal muscle cells, making skeletal muscle tissue responsive to estrogens (Lemoine, et al 2003, Wiik, et al 2005). There are indications that dramatically decreasing level of circulating 17β-estradiol (E 2 ) at the time of menopause contributes to age-associated muscle weakness (Phillips, et al 1993, Sipila, et al 2001. Our previous studies have shown that the use of estrogen-or estrogen and progesterone -based hormone replacement therapy (HRT) is associated with better muscle quality properties, such as a positive muscle-fat ratio within the muscle compartment, as well as improved muscle performance characteristics like muscle power and mobility (Ronkainen, et al 2009, Finni, et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is typically associated with deterioration of bone properties, reduced skeletal muscle mass and increased ectopic fat accumulation, which affect muscle quality and function. E2 deprivation has been shown to result in gain of fat mass and loss of fat free mass (Shea et al, 2015) as well as in increased risk for osteoporotic changes (Riggs, Khosla, & Melton, 2002;Szulc et al, 2006) while postmenopausal HRT partially counteracts aging related musculoskeletal deteriorations (Cheng et al, 2002;Komulainen et al, 1999;Sipilä et al, 2001;Taaffe et al, 2005). However, there is considerable variation in response to HRT between individuals, which can be partly explained by genetic factors (Langdahl, 2009).…”
mentioning
confidence: 99%